A STUDY OF SEMIOTICS ON CONNOTATIVE MEANING IN THE WORLD WIDE FUND FOR NATURE (WWF) ADVERTISING CAMPAIGN ON CLIMATE CHANGES - PUSPITA, AJENG RATNA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotics, Connotative Meaning, WWF, Advertising, Climate Changes. World Wide Fund for Nature (WWF) is one of the world's largest conservation  organizations established in more than 100 countries. WWF has more than 100 advertisements that aim to invite the community in protecting and preserving the environment and habitat. One themes from the advertisements is about climate change. Their advertisement usually uses an interesting images and utterances that have meanings inside it. In this study, the researcher analyzed these images and utterances based on the theory that it used. Furthermore, the researcher proposed two problems of the study, (1) What the signifier and signified found in the WWF advertisement campaign published under climate changes are (2) What the connotation meaning found in the WWF advertisement campaign published under climate changes is. This study uses a qualitative approach to uncover the occurrence in document analysis. The researcher applies the theory of Ferdinand de Saussure (quoted fromChandler, 2007, p.14) which divides the model of the sign into signifier and signified. The researcher also uses the theory of Roland Barthes (quoted in Chandler, 2007, p.137) which describe that in semiotics, denotation and connotation are terms that describe the relationship between the signified and the signifier.The study results shows that advertisement from the World Wide Fund for Nature(WWF) has signifier and signified differently in each advertisement. However, WWF has the same goal in making these advertisements that persuade people to concerned more about environmental issues and their habitats such as over fishing, global warming, illegal logging, and save animals from extinction.The researcher suggests the next researchers who want to do the same research andtheory use a different research subject participant. In the next studies, other researchers may be able to use movie, novels, brand products, or television advertising as the subject.